Mitochondrial Cardiomyopathies - El-Hattab, Ayman W.; Scaglia, Fernando (Frontiers in Cardiovascular Medicine, 2016)
Mitochondria are found in all nucleated human cells and perform a variety of essential functions, including the generation of cellular energy. Mitochondria are under dual genome control. Only a small fraction of their proteins are encoded by mitochondrial DNA (mtDNA) while more than 99% of them are encoded by nuclear DNA (nDNA). Mutations in mtDNA or mitochondria-related nDNA genes result in mitochondrial dysfunction leading to insufficient energy production required to meet the needs of various organs, particularly those with high energy requirements, including the central nervous system, skeletal and cardiac muscles, kidneys, liver, and endocrine system. Because cardiac muscles are one of the high energy demanding tissues, cardiac involvement occurs in mitochondrial diseases with cardiomyopathies being one of the most frequent cardiac manifestations found in these disorders. Cardiomyopathy is estimated to occur in 20-40% of children with mitochondrial diseases. Mitochondrial cardiomyopathies can vary in severity from asymptomatic status to severe manifestations including heart failure, arrhythmias, and sudden cardiac death. Hypertrophic cardiomyopathy is the most common type; however, mitochondrial cardiomyopathies might also present as dilated, restrictive, left ventricular noncompaction, and histiocytoid cardiomyopathies. Cardiomyopathies are frequent manifestations of mitochondrial diseases associated with defects in electron transport chain (ETC) complexes subunits and their assembly factors, mitochondrial tRNAs, rRNAs, ribosomal proteins, and translation factors, mtDNA maintenance, and coenzyme Q10 synthesis. Other mitochondrial diseases with cardiomyopathies include Barth syndrome, Sengers syndrome, TMEM70-related mitochondrial complex V deficiency, and Friedreich ataxia.